Procurement And Supply of Raw Ingredients For Pelus Fish (Anguilla Marmorata) at The Aik Nelengau Typical Eating Point In South Bengkulu District - Gion Gioneri Nurram; Herri Fariadi; Ana Nurmalia (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This study aims to analyze procurement, inventory levels, economic order quantity (EOQ), and factors influencing the stock of pelus fish (Anguilla marmorata) at Pondok Makan Khas Aik Nelengau, Seginim District, South Bengkulu Regency. Methodology: The research employs a quantitative descriptive method with multiple linear regression analysis. Results: Procurement is sourced from markets and subscriptions, with a volume of 20–30 kg/month and a price range of IDR 80,000–100,000/kg. The average inventory level scored 27.58 (high category). EOQ was 34.8 kg/month. Influencing factors include price (X1), raw material availability (X2), consumer preference (X3), demand for gulai (X4), and weather (X5), while distance (X6) was insignificant. Finding and Novelty: The study identifies EOQ and specific factors affecting pelus fish inventory. Originality: Offers insights into inventory management based on local raw materials. Conclusions: Optimizing pelus fish inventory management requires focusing on price, availability, and market demand. Type of Paper: Empirical Research Paper